Squeaking Is Common and Increases Over Time Among Patients With Long-term Follow-up After Ceramic-on-ceramic THA - Taniguchi, Kevin (Clin Orthop Relat Res, 2021)
BACKGROUND: Ceramic-on-ceramic (CoC) is a durable bearing with excellent wear characteristics, but squeaking remains a concern. The proportion of patients who report squeaking varies widely between studies performed at short- and mid-term follow-up. QUESTIONS/PURPOSES: (1) What proportion of patients treated with CoC THA bearings report squeaking at a minimum of 10 years of follow-up? (2) Are patient, implant, or radiographic factors associated with squeaking? (3) Are THAs that squeak more likely to be revised than those that do not? (4) Are patient-reported functional outcome scores lower between THAs that squeak and THAs that do not squeak at long-term follow-up? METHODS: Between January 1, 2003 and August 31, 2008 a total of 80 patients received THAs with third-generation alumina-on-alumina bearings at one center. Of the original 80 patients, 1% (1 of 80) had died, and 21% (17 of 80) were lost to follow-up before 10 years, leaving 62 patients for analysis at a median (range) of 14 years (11 to 16). Ceramic-on-ceramic THA represented 23% (80 of 343) of all primary THAs performed during the study period. Ceramic-on-ceramic THA was used preferentially in patients younger than 50 years of age. The mean (range) age of patients in the cohort was 44 ± 11 years (18 to 65). Sixty-eight percent (42 of 62) were men. Two separate manufacturers’ implants were included. There were uncemented acetabular and femoral components included in this study. All CoC bearings were third-generation alumina-on-alumina. Squeaking was determined through a mailed questionnaire or telephone interview. The 10-question survey developed by the researchers queried patients whether audible “squeaking” could be heard from their hip replacement. Patients were asked to write in their description of the noise to distinguish squeaking from other noises not relevant to the current study. Implant information, component position, and patient demographics were obtained via chart review and postoperative radiographs reviewed by one of the investigators not involved with the index operative procedure. Using revision for any reason as an endpoint, a Kaplan-Meier analysis was performed to compare survivorship between THAs that squeaked versus those that did not. Patient-reported outcomes were surveyed using the Hip Disability and Osteoarthritis Outcome Score for Joint Replacement (HOOS JR), which comprises six items regarding patient pain and function, raw summed scores range from 0 (perfect hip health) to 24 (total hip disability). RESULTS: Squeaking was self-reported by 53% (33 of 62) of patients in this group. Squeaking was more common in patients who received the titanium-molybdenum-zirconium-iron stem than in patients with the titanium-aluminum-vanadium stem (63% [29 of 46] versus 31% [4 of 13]; odds ratio 3.8 [95% CI 1.02 to 14.4]; p = 0.046). We found no differences in the likelihood a patient would report squeaking based on component position, component size, patient age, sex, or BMI. Ten-year survivorship free from revision was not lower in patients who reported squeaking (91% [95% CI 74 to 97] versus 90% [95% CI 71 to 96]; p = 0.69). Patient-reported outcome scores (HOOS JR) were not lower in those who reported squeaking (3 ± 3 [95% CI 1.5 to 4.0] versus 3 ± 5 [95% CI 1.5 to 5.5]; p = 0.59). CONCLUSION: At long-term follow-up, we found that CoC bearing squeaking in patients who underwent THA is more common than previously reported. Survivorship was lower than expected in this cohort, and most revisions in this series were for squeaking. Although implant-dependent, surgeons should counsel patients about the potential for squeaking in CoC THA, which may occur years after index procedure. LEVEL OF EVIDENCE: Level III, therapeutic study.